Bandwidth Enhancement of Rectangular Microstrip Patch Antenna using Defected Ground Structure - Dawit Fitsum; Dilip Mali; Mohammed Ismail (Institute of Advanced Engineering and Science, 2016)
This paper presents the bandwidth enhancement of a Proximity Coupled Feed Rectangular Microstrip Patch Antenna using a new Defected Ground Structure - an ‘inverted SHA’ shaped slot on the ground plane of the proximity coupled feed rectangular Microstrip patch antenna. The parameters such as Bandwidth, Return loss, VSWR and Radiation efficiency are improved in the proposed antenna than simple proximity coupled feed rectangular Microstrip patch antenna without Defected Ground Structure. A comparison is also shown for the proposed Microstrip patch antenna with the antenna structure without Defected Ground Structure. The proposed antenna resonates in S-band at frequency of 2.4 GHz with bandwidth of 180 MHz. A very good return loss of -47.9223 dB is obtained for the Microstrip patch antenna with an ’inverted SHA’ shaped Defected Ground Structure. Implementing an ‘inverted SHA’ shaped defect in the ground plane of the proximity coupled feed rectangular Microstrip patch antenna results in 5.3% improvement in bandwidth with 16.01% reduction in the overall area of the ground plane as compared to the Microstrip patch antenna without Defected Ground Structure.